The Influence of Service Quality of the Mobile JKN Application on the Satisfaction of BPJS Kesehatan Participants - Sa’adah, Hidayana; Irawan (CV Raskha Media Group, 2025)
This study aims to analyze the effect of service quality and system quality on user satisfaction with the Mobile JKN application. The study employs a quantitative approach using primary data collected through questionnaires distributed to 100 Mobile JKN users. The sampling technique applied is purposive sampling. Data analysis is conducted using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS. The results indicate that service quality has a positive and significant effect on user satisfaction. In addition, system quality also has a positive and significant effect on user satisfaction. However, system quality does not have a significant effect on service quality. These findings suggest that user satisfaction with the Mobile JKN application is influenced by both perceived service quality and system quality. Therefore, continuous improvement of service quality and system quality is necessary to enhance user satisfaction with the Mobile JKN application